MANAJEMEN K13 DALAM MENINGKATKAN PROSES PEMBELAJARAN AL-QUR’AN DI SD MUHAMMADIYAH 23 SEMANGGI SURAKARTA SOSROKARTONO - Achmad Sudibyo; Badarudin (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2023)
The 2013 curriculum is a learning system or approach that involves several disciplines to provide broad experience and knowledge to students. The 2013 curriculum is more than character education, especially at the basic level, which will be the foundation for the next level. Character education in the 2013 curriculum aims to improve the quality of the learning process and educational outcomes that lead to good character and morals of students, and in balance with the competency standards of graduates from each educational unit. And in the implementation of the 2013 curriculum, character education can be included in all fields of study contained in the curriculum. This research is qualitative in nature by formulating concepts from philosophical, theoretical and practical implementation. The researcher started this research by collecting research materials and data, analyzing and then formulating the updated knowledge. The results of the K13 Management research in improving the learning process of the Qur'an is to allocate sufficient time for learning the Qur'an, which is four hours every week and added 30 minutes at the beginning of each lesson. Based on the curriculum book for SD Muhammadiyah 23 Semanggi, it is stated that the time allocation for learning the Qur'an is four hours of lessons for one week. In addition, the principal also allocates time for al-Qur'an subjects every day from 07.00 to 07.30 WIB for joint tadarus between teachers and students in their respective classes. Keywords : Curriculum, K13, Al-Qur'an, Management, Golden Age